![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
3个回答
展开全部
(√a+1/√a)²-(√a-1/√a)²
=【(√a+1/√a)-(√a-1/√a)】【(√a+1/√a)+(√a-1/√a)】
=2/√a×2√a
=4
=【(√a+1/√a)-(√a-1/√a)】【(√a+1/√a)+(√a-1/√a)】
=2/√a×2√a
=4
追问
用两种回答
追答
(√a+1/√a)²-(√a-1/√a)²
=a+2+1/a-(a-2+1/a)
=a+2+1/a-a+2-1/a
=4
展开全部
(√a+1/√a)²-(√a-1/√a)²
=a+1/a+2-a-1/a+2
=4
(√a+1/√a)²-(√a-1/√a)²
=(√a+1/√a+√a-1/√a)(√a+1/√a-√a+1/√a)
=4
=a+1/a+2-a-1/a+2
=4
(√a+1/√a)²-(√a-1/√a)²
=(√a+1/√a+√a-1/√a)(√a+1/√a-√a+1/√a)
=4
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
(√a+1/√a)²-(√a-1/√a)²
=(a+1+2√a)/a-(a+1-2√a)/a
=[(a+1+2√a)-(a+1-2√a)]/a
=4√a/a
=(a+1+2√a)/a-(a+1-2√a)/a
=[(a+1+2√a)-(a+1-2√a)]/a
=4√a/a
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询